2020
DOI: 10.1002/jcc.26134
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of the dianionic phosphate group: Validation on the recognition site of the homodimeric enzyme phosphoglucose isomerase

Abstract: We calibrate and validate the parameters necessary to represent the dianionic phosphate group (DPG) in molecular mechanics. DPG is an essential fragment of signaling biological molecules and protein-binding ligands. It is a constitutive fragment of biosensors, which bind to the dimer interface of phosphoglucose isomerase (PGI), an intracellular enzyme involved in sugar metabolism, as well as an extracellular protein known as autocrine motility factor (AMF) closely related to metastasis formation. Our long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…Further refinements could be sought. Thus E MTP * could be possibly improved if, as mentioned in Devillers et al 39 a greater weight than is presently the case were conferred to the charge‐quadrupole component of the penetration, which depends upon a general coefficient intervening in the exponential of this component independent of the effective atomic radii for E pen . This has been done, in the context of SAPT analyses for water calibration at the correlated level 60 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Further refinements could be sought. Thus E MTP * could be possibly improved if, as mentioned in Devillers et al 39 a greater weight than is presently the case were conferred to the charge‐quadrupole component of the penetration, which depends upon a general coefficient intervening in the exponential of this component independent of the effective atomic radii for E pen . This has been done, in the context of SAPT analyses for water calibration at the correlated level 60 .…”
Section: Discussionmentioning
confidence: 95%
“…51 We have resorted to the first two functionals consistent with previous SIBFA validation studies on multimolecular complexes. 32,[38][39][40][41] The choice of the ω-B97XD functional was motivated by a recent study SAPT-DFT study 52 on the complexes of water with Zn(II) and F À which showed this functional to be the one enabling the closest agreement to SAPT-DFT. The BSSE 53 correction was applied to all QC calculations.…”
Section: Introductionmentioning
confidence: 99%
“…This work opens a new avenue for condensed phase simulations of complex systems as both the non-additivity and the non-isotropy of the SIBFA potential were amply validated in numerous previous studies from our Laboratories. 2,[76][77][78][79][80][81][82][83][84][85] This should ensure for a safe transferability, from the training set data to proteins and nucleic acids. At this stage, it is important to note that the simple AMOEBA intramolecular potential used in this study is not optimal since its ideal bond angle was set to 108.5 • .…”
Section: Discussionmentioning
confidence: 99%
“…In order to ensure better control of the nonadditivity of E pol , we have included in the optimization procedure the 10 complexes of TZT with the monozinc cores, that is, each of the His3 and Asp-Cys-His cores in their structures extracted from their complexes with each of the five inhibitors. As in previous studies, 33,64 we have similarly resorted to a Zn(II) "probe" to maximize the response of the probed ligands regarding both first-order (Coulomb and exchange), and second-order (polarization and charge-transfer) responses. Thus, benzocarboxylate was probed by Zn(II) approaching one anionic carboxylate upon performing in-plane radial and angular variations, and radial variations along a perpendicular to the plane passing through this oxygen, or to the extracyclic C atom or the C atoms ortho, para or meta to it.…”
Section: Refinements Of the Tzt Benzocarboxylate And Imidazole Frmentioning
confidence: 99%
“…In light of the comparisons with the QC results on the extended recognition site, we sought for further refinements of the relevant parameters for TZT, for the benzocarboxylate arm (an R2 substituent in four of the five considered inhibitors), but also for imidazole, which occurs four times out of six as a Zn‐ligand in the dizinc binding core of VIM‐2. We have resorted to a procedure recently integrated into the standard SIBFA software and used to calibrate the dianionic phosphate group (DPG) 64 and to derive a water potential grounded on SAPT for MD simulations on liquid water [Naseem‐Khan et al, to be submitted]. The relevant fragment specific parameters for the SIBFA E MTP , E rep , E pol , and E ct contributions were optimized by LSQF minimization of the error with respect to their respective RVS counterparts E C , E X , E pol , and E ct as computed in all probed positions of the fragment.…”
Section: Computational Proceduresmentioning
confidence: 99%